P281 A serum biomarker panel can accurately identify the presence of mucosal ulcers in patients with Crohn's disease. (15th January 2020) - HOLMER, A; Boland, B; Singh, S; Neill, J; Le, H; Miralles, A; Collins, A; Sandborn, W; Dulai, P
Abstract: Background: Ulcer healing is the primary endoscopic treatment target in Crohn's disease (CD) in routine practice. A novel serum-based biomarker panel named endoscopic healing index (EHI, Monitr, Prometheus Biosciences, San Diego, CA) was developed and validated for identifying mucosal inflammation as assessed by the simple endoscopic score for CD (SES-CD). 1 We aimed to define the operating characteristics of EHI in routine practice for mucosal ulcers specifically. Methods: EHI was analysed on serum samples paired with endoscopies from adult patients (≥18 years) participating in a prospective biobank (June 2014 to December 2018). Patients with an ileal pouch-anal anastomosis or an ileostomy were excluded. The performance of EHI for endoscopic disease activity was evaluated for subcomponents of SES-CD scores (0–60) including ulcer presence and size, extent of ulcerated surface, extent of affected surface, and presence of strictures. Diagnostic performance was assessed using previously identified cut-offs for optimal EHI performance in CD for ruling out endoscopic activity (20 points) and ruling in endoscopic activity (50 points). Logistic regression was performed to identify confounders of EHI (patient factors, disease characteristics) and for the strength of association between EHI and ulcers (presence, size). Results: A total of 205 CD patients were included in the analysis (50% male, median age 37 years). EHI values were significantly higher with increasing ulcer size ( p < 0.001). An EHI cut-off of 20 points exhibited modest sensitivity for ruling out any ulcers (85%, 95% CI 77–91), and large (0.5–20 mm) or very large (>20 mm) ulcers specifically (92%, 95% CI 84–97). An EHI cut-off of 50 points had modest specificity for ruling in the presence of any ulcers (85%, 95% CI 76–92), and large or very large ulcers specifically (87%, 95% CI 79–92). After accounting for the total extent of inflamed mucosa, extent of strictured mucosa, and disease location, each 20-point increase in EHI was independently associated with an incremental 1.7-fold increased probability for the presence of a large or very large ulcer (aOR 1.7, 95% CI 1.1–2.6). Conclusion: EHI values were associated with ulcer size independent of inflammatory or stricture burden, and accurately identified the presence of ulcers and large or very large ulcers specifically. A cut-off of 50 points can reliably rule in the presence of ulcers and allow for treatment adjustment without endoscopy. A cut-off of 20 points can reliably rule out the presence of ulcers and signal completion of treatment adjustment algorithms. Reference: D'Haens G et al. Gastroenterology, 2019, In Press.